Articles in english as a second language : a phraseological perspective - Lesniewska, Justyna (Jagiellonian University Press, 2020)
The aim of this study is twofold: firstly, to provide an overview of research findings on the acquisition and use of articles in English as a second language; secondly, to investigate this issue from a phraseological perspective. The book also presents an examination of various linguistic accounts of the English article system with respect to their application to English language teaching. In view of the growing body of theoretical and empirical studies indicating that language use is to a considerable degree phraseologically motivated, this book argues for a connection between formulaicity and correct article use. This possibility is explored in two studies presented in the final chapter, which suggest that correctness in the use of articles depends on the frequency of the phrases in which they appear. These findings support the view that frequency-driven conventionality in language may play a role in the acquisition and use of articles in L2 English.
Keywords: English language -- Article.; English language -- Study and teaching.; Anglais (Langue) -- Étude et enseignement.; FOREIGN LANGUAGE STUDY / English as a Second Language.; English language -- Study and teaching; English language -- Article; Language and languages -- Study and teaching